2017
DOI: 10.1186/s12967-017-1212-x
|View full text |Cite|
|
Sign up to set email alerts
|

The progressive fragmentation of the KIT/PDGFRA wild-type (WT) gastrointestinal stromal tumors (GIST)

Abstract: Recent advances in molecular biology have revolutionized the concept of KIT/PDGFRA wild type (WT) gastrointestinal stromal tumors (GIST) than the past. Indeed, from being defined as GIST without KIT or PDGFRA mutations, we are now faced with the opposite scenario, where KIT/PDGFRA WT GIST are “positively” defined according to their specific molecular alterations. In particular, if until recently KIT/PDGFRA GIST without abnormalities of KIT, PDGFRA, SDH, and the RAS signaling pathway were referred as quadruple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 35 publications
0
54
0
Order By: Relevance
“…Quadruple-WT GIST represent an undefined and heterogeneous category of tumors (15,27), that inevitably poorly respond to standard treatments, represented by TKI, due to the lack of the target oncogenic alteration. The detection of a significant fraction of this subgroup as carrier of actionable KIT mutations not only advocates the routine implementation of next generation sequencing approaches in the current molecular diagnostic protocols, but also opens new and effective therapeutic strategies for these patients, that are actually devoid of active pharmacological opportunities.…”
Section: Discussionmentioning
confidence: 99%
“…Quadruple-WT GIST represent an undefined and heterogeneous category of tumors (15,27), that inevitably poorly respond to standard treatments, represented by TKI, due to the lack of the target oncogenic alteration. The detection of a significant fraction of this subgroup as carrier of actionable KIT mutations not only advocates the routine implementation of next generation sequencing approaches in the current molecular diagnostic protocols, but also opens new and effective therapeutic strategies for these patients, that are actually devoid of active pharmacological opportunities.…”
Section: Discussionmentioning
confidence: 99%
“…In a phase II trial with Simon two-stage design, no objective response was observed in the first nine patients, and vandetanib was thus considered inactive 37. In wild-type GIST patients with competent SDH, 4%–13% carried the BRAF V600E mutation 38. One case report described a response to the BRAF inhibitor in a patient with BRAF V600E-mutated GIST 39…”
Section: Part 1 Developed Genomic-guided Precision Therapy For Stsmentioning
confidence: 99%
“…More than 10 years have passed since the GIST community defined a new molecular profile that inevitably leads, over time, to the disappearance of KIT/ PDGFRA WT GIST that was emerging as a group of heterogeneous distinct entities with multiple molecular alterations. (2,3) KIT/PDGFRA WT GISTs include at least 5 main subgroups: Succinate deyhidrogenase (SDH)-deficient GISTs mainly characterized by A, B, C, and D gene mutations; RAS pathway-mutated GISTs, with mutations in neurofibromatosis 1, BRAF or K-RAS; fibroblast growth factor receptor (FGFR) pathway-deregulated GISTs; Neutrophic tropomyosin receptor kinase (NTRK)-positive GISTs; and the pan-WT GIST/all negative WT GIST.…”
Section: To the Editormentioning
confidence: 99%